Social rights jurisprudence. Emerging trends in international and comparative law (Cambridge, 2009)
"In the space of two decades, social rights have emerged from the shadows and margins of human rights jurisprudence. The authors in this book provide a critical analysis of almost two thousand judgments and decisions from twenty-nine national and international jurisdictions. The breadth of the decisions is vast, from the resettlement of evictees to the regulation of private medical plans to the development of state programs to address poverty and illiteracy. The jurisprudence not only implicates our understanding of economic, social, and cultural rights, but also challenges the philosophical debates that question whether these rights can and should be justiciable. "